Empirical Study Of Stress Level Of Teacher’s In Government & Private Schools In Chhattisgarh (Journal of Namibian Studies : History Politics Culture, 2023)
The study investigates the stress levels of school-employed women instructors in Raipur, using a normative survey approach. The sample consisted of 60 teachers from three government and private schools. The research found a significant relationship between teachers' salaries and stress levels. The study also revealed significant differences in stress levels and distance traveled to their workplaces. Additionally, stress among teachers and interpersonal conflict among instructors were found to differ significantly. The findings highlight the need for improved training and support for female teachers in the field.